Md-miR156ab and Md-miR395 Target WRKY Transcription Factors to Influence Apple Resistance to Leaf Spot Disease - Zhang, Qiulei; Li, Yang; Zhang, Yi; Wu, Chuanbao; Wang, Shengnan; Hao, Li; Wang, Shengyuan; Li, Tianzhong (Frontiers in Plant Science, 2017)
MicroRNAs (miRNAs) are key regulators of gene expression that post-transcriptionally regulate transcription factors involved in plant physiological activities. Little is known about the effects of miRNAs in disease resistance in apple (Malus×domestica). We globally profiled miRNAs in the apple cultivar Golden Delicious (GD) infected or not with the apple leaf spot fungus Alternaria alternaria f.sp. mali (ALT1), and identified 58 miRNAs that exhibited more than a two-fold upregulation upon ALT1 infection. We identified a pair of miRNAs that target protein-coding genes involved in the defense response against fungal pathogens; Md-miR156ab targets a novel WRKY transcription factor, MdWRKYN1, which harbors a TIR and a WRKY domain. Md-miR395 targets another transcription factor, MdWRKY26, which contains two WRKY domains. Real-time PCR analysis showed that Md-miR156ab and Md-miR395 levels increased, while MdWRKYN1 and MdWRKY26 expression decreased in ALT1-inoculated leaves; furthermore, the overexpression of Md-miR156ab and Md-miR395 resulted in a significant reduction in MdWRKYN1 and MdWRKY26 expression. To investigate whether these miRNAs and their targets play a crucial role in plant defense, we overexpressed MdWRKYN1 or knocked down Md-miR156ab activity, which in both cases enhanced the disease resistance of the plants by upregulating the expression of the WRKY-regulated pathogenesis-related (PR) protein-encoding genes MdPR3-1, MdPR3-2, MdPR4, MdPR5, MdPR10-1, and MdPR10-2. In a similar analysis, we overexpressed MdWRKY26 or suppressed Md-miR395 activity, and found that many PR protein-encoding genes were also regulated by MdWRKY26. In GD, ALT-induced Md-miR156ab and Md-miR395 suppress MdWRKYN1 and MdWRKY26 expression, thereby decreasing the expression of some PR genes, and resulting in susceptibility to ALT1.